PENGARUH MODEL PEMBELAJARAN PROBLEM POSING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VII SMPN 8 PAYAKUMBUH - Putri, Desy Tri Wirlia (Departemen Matematika, 2023)
In the study of mathematics, the ability to solve mathematical problems is a very important skill. Based on the results of the Final Semester Examination and an initial test of mathematical problem-solving abilities, it appears that class VII at SMPN 8 Payakumbuh still lack the ability to solve mathematical problems. The problem-posing learning model is the ideal model for improving students' mathematical problem-solving abilities. The descriptive and quasi-experimental design of this kind of research employs a Randomized Control Group Only Design. Simple Random Sampling was used for the sampling. as the experimental and control classes, VII.1 and VII.5. The experimental class is the subject of this study. The study's findings include P-Value = 0.010 =0.05, H0 is rejected, and it is concluded that students in class VII SMPN 8 Payakumbuh Academic Year 2022/2023 who learn with a problem-posing model have better mathematical problem-solving abilities than conventional learning model.Keywords. – Mathematical Problem-Solving Abilities, Problem Posing